Community Participation in the Village Climate Program to Anticipate Future Climate Change in Wetlands. Issue 1 (June 2020) - Nasruddin,; Kumalawati, R; Syaharuddin,; Yuliarti, A; Rajiani, I
Abstract: The issue of global warming and climate change is a crucial problem in the world as it triggers an increase in temperature and disasters. Indonesia one of the countries most vulnerable to climate change impacts. The impact of climate change is increasing every year. Efforts to reduce the impact of climate change on environmental management through climate village. Community participation is an important aspect of the success of the climate village program. The purpose of this study is how the Community Participation in the Village Climate Program to Anticipate Future Climate Change in Wetlands. This research method is quantitative. Sources of data in this study are primary data and secondary data. Sources of primary data obtained through interviews. Secondary data sources in the form of documentation and official archives that can support the research. Population and sample in the community in the village climate. Processing of data from interviews calculated percentages based on criteria of severe, moderate and good. Data in scoring with Likert scale approach and wide intervals. The analysis is based on the theory of Miles and Huberman. The findings of the study were to determine the Community Participation in the Village Climate Program to Anticipate Future Climate Change in Wetlands. Limitations of the study limit community participation in the climate village program. Community participation in the program is limited to mitigation and adaptation. The results showed community participation in the mitigation activities has been "good" and should be improved. Community participation in the activities of adaptation is "moderate". This participation still needs improvements to community participation in the activities of adaptation to climate change can be better. Community participation is an important aspect of the success of the climate village program. Success climate village programs can reduce the negative impacts of future climate change on wetlands.